Perspectives on Civil Law and the Canon Law of the Catholic Church in a Multireligious Society - Winga, Kristantino; Rupi, Damianus Ngai (Hanifiya: Jurnal Studi Agama-Agama, 2024)
This research aims to explore the views of civil law and the Code of Canon Law regarding interfaith marriages, as well as their impact on individuals and society, especially in the Indonesian context. The method used is a comparative study, which allows an in-depth understanding of interfaith marriages. Interfaith marriage is a complex phenomenon with various legal implications, especially in the context of civil law and the Code of Canon Law of the Catholic Church. The background to this problem includes the growing differences in religious beliefs and practices in society, which has resulted in lawsuits regarding interfaith marriages. The results of the study reveal differences in civil law approaches, which tend to be secular and focus on legal aspects, while the Catholic Church's Code of Canon Law emphasizes spiritual and theological components. In the context of interfaith marriages, individuals entering into interfaith marriages face challenges in integrating two different beliefs. The conclusions of this study speak to the need for interfaith dialogue and collaboration between civil and church authorities to develop a more inclusive approach to interfaith marriage. Implementing policies that pay attention to legal and spiritual aspects can create a framework that supports diversity and social cohesion in an increasingly pluralistic society.